Aplikasi Animasi Edukasi Anatomi Tubuh Manusia Dalam Bahasa Arab Pada Sd Ababil Kota Pagar Alam Berbasis Android - Tri Susanti Santi (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
This study aims to produce an Educational Application of Anatomy of the Human Body in Arabic in the SD Ababil City of the Android-Based Natural Fence City to suppress the effectiveness of the learning process and measure student learning outcomes at home. Based on the results of data collection using the method of interview and observation that in this study learning still uses the medium of books to study at home. the learning process will certainly reduce the effectiveness of parents in teaching and takes a long time which makes children less interested in learning at home. This application was developed using Adobe Flash Professional CS6 software. This research uses the ADDIE system development method because this method is easier to understand and has good product development stages in accordance with this research. Based on the results of expert reviews that have been conducted shows an average value of 4.3 with a very valid category. Then based on the results of the field test or alpha and beta tests obtained from the results of the pretest and posttest the average student produces a value of 86.0 with the High category. The expected results of this study are in the form of an animated application of anatomy education of the human body in Arabic on the Android-based Ababil Pagar Alam city based on Android which can be used to help the learning process so that it makes it easier to understand the material especially the types of limbs.